AN OBSERVATION ON PRIMARY PRODUCTIVITY AND ECOLOGY OF KARANJA CREEK, MAHARASHTRA, INDIA - Garima; A. K. Jaiswar; A. T. Landge; G. Deshmukhe (Journal of Indian Fisheries Association, 2018)
Karania creek of Dharamtar confluence was assessedfor primary productivity in terms of phytoplankton abundance and concentration of chlorophyll-a. High chlorophyll-a value was observed in September followed by April. In October month, the impact of anthropogenic activities, was witnessed in form of bloom Skeletonema coastatum. A total 56 genera of phytoplankton were recorded, among which most dominant group was diatoms followed by dinoflagellates and blue green algae. Dinoflagellates were more common in the inner parts of the creek while blue green algae were found during the influence of monsoon. The diversity of phytoplankton was found to be higher in outer part of creek. However, the study suggests healthy condition of the coastal ecosystem but the threat from anthropogenic activities cannot be ruled out.